Performance measurement of main memory database recovery algorithms based on update-in-place and shadow approaches - Kumar, V.; Burger, A. (IEEE transactions on knowledge and data engineering, 1992)
The authors present a performance study of two main memory database recovery algorithms, one using a shadow approach and the other update-in-place. The results show that in main memory databases, shadow approach performs better than update-in-place. The authors introduce minor improvements to the shadow scheme and show that the modified algorithm does show further performance improvement.< >